2001
DOI: 10.2351/1.1404415
|View full text |Cite
|
Sign up to set email alerts
|

Use of “assist” gas in the laser drilling of titanium

Abstract: A series of experiments is reported which investigate the effect of an ''assist'' gas on the single-pulse Nd:YAG laser drilling of titanium. Hole breakthrough percentages are determined for arrays of holes drilled without an assist gas and with assist gasses of different pressures and compositions. Breakthrough percentages are given as functions of laser pulse energy for various thicknesses of material under different assist gas conditions. Regimes are identified in which the use of a gas assists drilling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
(2 reference statements)
1
11
0
Order By: Relevance
“…Therefore, most of the molten metal escapes from the top of the drilled hole, eroding the hole wall in the process and resulting in higher entry diameter. This explanation is also consistent with the work of Rodden et al [24] who reported that, for single shot drilling at low energy densities, the melt ejection is effectively from the top of the surface before hole breaks through from the bottom. Subsequent increase in pulse energy helps in advancement of the melt front, increases the exit hole diameter and results in ejection of the material from the bottom surface.…”
Section: Dependence On Characteristics Of Individual Drilled Holessupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, most of the molten metal escapes from the top of the drilled hole, eroding the hole wall in the process and resulting in higher entry diameter. This explanation is also consistent with the work of Rodden et al [24] who reported that, for single shot drilling at low energy densities, the melt ejection is effectively from the top of the surface before hole breaks through from the bottom. Subsequent increase in pulse energy helps in advancement of the melt front, increases the exit hole diameter and results in ejection of the material from the bottom surface.…”
Section: Dependence On Characteristics Of Individual Drilled Holessupporting
confidence: 90%
“…Therefore, the characteristics of the individual hole play a key role in determining cut quality. Rodden et al [24] reported on the effect of assist gas on single pulse laser drilling of titanium. Prior work in the authors' laboratory [25] has also included studies on pulsed Nd:YAG laser drilling of Ni-base and Ti alloys.…”
Section: Introductionmentioning
confidence: 99%
“…An additional unknown, not addressed by the model, is the effect of the physical properties of the oxide film on the droplet trajectory and velocity. To complicate matters further, there is published evidence [44] that the assist gas has a decelerating effect on the ejected droplets. To account for this an additional decelaration term would have to be added to Eq.…”
Section: Melt Ejection Velocitymentioning
confidence: 98%
“…Combining Eqs. (42)- (44), the power lost due to cooling by the assist gas, P conv , within the melt surface area can be written as…”
Section: Energy Balancementioning
confidence: 99%
“…The melt expulsion is recognized as the most efficient material removal mechanism at the lower laser powers [4,5]. In most of the laser drilling applications, coaxial assist gases are used to facilitate the melt expulsion, protect the surface oxidation, and shield the focusing lens [6]. Contrary to intuition, however, the increase in assist gas pressures actually increases the laser drilling time at all laser power levels [7,8].…”
Section: Introductionmentioning
confidence: 98%